A Semiotic Analysis In Bon Jovi Selected Songs - Jahida, Stris Jumiyanti; Katili, Adriansyah A.; Podungge, Rusni (Jurnal Bahasa, Sastra, dan Budaya, 2025)
Song lyrics as a form of artistic expression that is full of meaning are often used as a tool to convey deep messages that are close to human life. One of the famous rock bands, Bon Jovi is known for its inspiring and meaningful song lyrics. The author's interest in the meanings contained in Bon Jovi's song lyrics, especially in the songs "It's My Life," "Have a Nice Day," and "We Weren't Born to Follow", prompted this study. This research aims to determine the meaning of Bon Jovi's song lyrics by describing the signifiers and signified contained therein. This study uses a qualitative descriptive method with a Saussure semiotic approach. This study uses Saussure's Semiotic theory, which identifies the signifiers and signified in the lyrics, followed by syntagmatic and paradigmatic analysis to understand the relationship between sentences and reveal the deeper meaning of the song. Rhyme analysis is also used to strengthen the interpretation of the overall meaning of the song. The results of the study show that the three songs have a central theme of individual freedom and rejection of external control. The lyrics emphasize the importance of following one's desires and not letting others control one's life. Never give up on facing the challenges in our lives and continue to struggle to achieve our dreams without being influenced by others.